The influence of biased exposure to forgone outcomes. (8th January 2020) - Plonsky, Ori; Teodorescu, Kinneret
Abstract: After making decisions, we often get feedback concerning forgone outcomes (what would have happened had we chosen differently). Yet, many times, our exposure to such feedback is systematically biased. For example, your friends are more likely to tell you about a party you missed if it was fun than if it was boring. Despite its prevalence, the effects of biased exposure to forgone outcomes on future choice have not been directly studied. In three studies (five experiments) using a simplified learning task, we study the basic influence of biased exposure to forgone outcomes in the extreme case in which decision makers can easily infer the missing information such that the biased exposure carries almost no informational value. The results in all studies suggest that nevertheless, the biased exposure to forgone outcomes affected choice. Exposure to forgone outcomes only when they were better than the obtained outcomes (Only‐Better‐Forgone) increased selections of the forgone option compared with exposure to forgone outcomes only when they were worse than the obtained outcome (Only‐Worse‐Forgone). Moreover, relative to an unbiased exposure to all forgone outcomes, the effect of exposure to Only‐Worse‐Forgone was larger than the effect of exposure to Only‐Better‐Forgone feedback. However, these effects were not universal: In environments that include rare negative events ("disasters"), biased exposure to forgone outcomes had very little effect. We raise potential explanations and further discuss implications for marketing and risk awareness.